The Implementation of Lesson Study in Teaching Mathematics in Region 3, Cluster XI South Palu - Renawati, Renawati; Idris, Mustamin; Jaeng, Maxinus (Jurnal Universitas Tadulako, 2023)
This research is a descriptive study with a qualitative approach, which aims to describe the application of Lesson Study in mathematics learning to teachers and students in Region 3 Cluster XI Palu Selatan. Lesson Study is effectively applied in learning mathematics. This can be proven from the results of interviews which explain that the application of lesson study in learning mathematics can be understood by most of the teachers who are members of the 3 Cluster XI area of South Palu. In addition, the results obtained in the activity plan are lesson plans, media used in learning, learning modules, and observation sheets. In the activities carried out there are three important activities, namely the activities of the teacher carrying out mathematics learning in mixed arithmetic operations, observers observing learning, and students in learning. In the listening activity, the model teacher starts the discussion by conveying his impressions, experiences, opinions about the implementation of the learning he has carried out.